Classification of Cryptocurrency: A Review of the Literature - et. al., Wan Nur Izzah Wan Muhamad Fokri, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Technological development has affected the global financial industry. The use of digital currency is increasingly gaining a place among the world’s population, so much so that there are 2486 types of digital currency on record. Scholars in Islamic finance as well as Fatwa institutions all over the world have delivered their religious decree concerning the digital currency; hence, most discussions about the use of the decree was only directed at Bitcoin as a medium of payment although some digital currencies have other functions, such as being utility and security tokens. Therefore, the decree concerning other digital currencies cannot apply the decree issued for Bitcoin only because each digital currency has a different conceptual framework. Hence, this study, which applied the qualitative approach and a descriptive research design, intended to analyse the classification of digital currencies according to their function and characteristics. The findings show that digital currency is classified into coins, currency, tokens, payment tokens, utility tokens and security or asset tokens. Coins function as a medium of payment and store of value that was developed using its own blockchain. Currency is a medium of exchange and can be exchanged with any form of money, including the crediting or debiting of an account. Tokens represent services, financial instruments or infrastructure that is developed using the blockchain technology of other digital currencies. Tokens are divided into three types according to their function, namely payment tokens, utility tokens and security or asset tokens. The classification of digital currencies provides a guideline for the public who wish to carry out transactions using digital currencies. It is important to ensure that transactions carried out in accordance with the syarak will help alleviate cases of fraud related to investment and sale of digital currencies.